2016
DOI: 10.1080/10715762.2016.1253833
|View full text |Cite
|
Sign up to set email alerts
|

Increased non-protein bound iron in Down syndrome: contribution to lipid peroxidation and cognitive decline

Abstract: Down syndrome (DS, trisomy 21) is the leading cause of chromosomal-related intellectual disability. At an early age, adults with DS develop with the neuropathological hallmarks of Alzheimer's disease, associated with a chronic oxidative stress. To investigate if non-protein bound iron (NPBI) can contribute to building up a pro-oxidative microenvironment, we evaluated NPBI in both plasma and erythrocytes from DS and age-matched controls, together with in vivo markers of lipid peroxidation (F-isoprostanes, F-dih… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…According to a recent paper, DS patients show increased levels of serum ferritin but decreased levels of Tf. Furthermore, despite a slight reduction of total iron content, increased levels of free redox-active iron in both plasma and erythrocytes were found [90]. In addition, increased iron levels were significantly associated with increased lipid peroxidation products such as F2-isoprostane and a worsening of cognitive functions [90].…”
Section: Iron Dysmetabolism In Down Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…According to a recent paper, DS patients show increased levels of serum ferritin but decreased levels of Tf. Furthermore, despite a slight reduction of total iron content, increased levels of free redox-active iron in both plasma and erythrocytes were found [90]. In addition, increased iron levels were significantly associated with increased lipid peroxidation products such as F2-isoprostane and a worsening of cognitive functions [90].…”
Section: Iron Dysmetabolism In Down Syndromementioning
confidence: 99%
“…Furthermore, despite a slight reduction of total iron content, increased levels of free redox-active iron in both plasma and erythrocytes were found [90]. In addition, increased iron levels were significantly associated with increased lipid peroxidation products such as F2-isoprostane and a worsening of cognitive functions [90]. In agreement, a previous study comparing DS and DS/AD subjects showed increased plasma ferritin concentration in DS/AD, and the authors proposed that the onset of AD-like dementia in DS may possibly be related to the increased uptake and deposition of iron following alteration in plasma iron transport [91].…”
Section: Iron Dysmetabolism In Down Syndromementioning
confidence: 99%
“…Moreover, AdA oxidation form four series of regioisomers (7-, 10-, 14-, and 17-series) [ 31 ], and were detected in AD patients [ 31 , 32 ], and also in Rett syndrome (RTT) [ 25 ], Down syndrome [ 33 ], and epileptic [ 34 ] patients. The myelin sheath is concentrated with AdA and F 2 -dihomo-IsoPs have been suggested to be specific in assessing the extent of free radical damage of the myelin [ 31 ].…”
Section: Relevance Of Lipid Peroxidation Products In Neurodegeneramentioning
confidence: 99%
“…This is mainly due to the limited availability of purified molecules to be used as reference compounds in the identification of isoprostanoids in biological samples, which is an indispensable step in the exploration of the cause-effect relationship between the neurological damage and the levels of isoprostanoids in the bloodstream or in other fluids and tissues. Nevertheless, assays performed in plasma or urine samples are proving useful to predict clinical presentation/evolution of neurological diseases [ 25 , 27 , 31 , 32 , 33 , 34 , 38 , 52 , 57 , 59 , 69 , 70 ] ( Table 2 ). Plasma 10-F 4t -NeuroP and 4-F 4t -NeuroP levels were shown to be useful to discriminate between different brain diseases and the association to clinical severity appeared to be distinctive for different neurological conditions, thus suggesting that in vivo DHA oxidation follows preferential chemical rearrangements according to different human brain diseases.…”
Section: In Search Of a Biomarker: Isoprostanoids As Biomarkers Inmentioning
confidence: 99%
“…The dyshomeostasis of intrinsic metals, such as zinc, copper, and iron, may play a role in cognitive impairment in individuals with DS, as intersectin 1 coded in the trisomic region in DS is suggested to be involved in iron internalization. Indeed, increases in the levels of non-protein-bound iron in serum and iron-binding protein lactotransferrin in the brain have been demonstrated in individuals with DS [48,49]. Other ‘-omics’ analyses, such as metabolomic and elementomics analyses, for DS samples are expected to help unravel the pathophysiological mechanisms underlying abnormalities in the DS brain.…”
Section: Other ‘-Omics’ Analysesmentioning
confidence: 99%